An Examination of Administrators’ Nonrevenue, Olympic Program Values within NCAA Athletic Departments - Cooper, Coyte Gene; Weight, Erianne A. (Journal of Intercollegiate Sport, 2011)
The presence of the arms race in intercollegiate athletics has led to extensive spending on major, revenue-producing sports (Knight Commission, 2004). Despite the fact that only a handful of men’s basketball and football programs produce profits (NCAA, 2009), administrators continue to embrace a commercial model that has coincided with the elimination of nonrevenue, Olympic sports in National Collegiate Athletic Association (NCAA) athletic departments. With this in mind, the purpose of the study was to gain an understanding of the nonrevenue, Olympic program elements that were most highly valued by NCAA Division I, II, and III athletic administrators (N = 435) to facilitate an effort to develop strategic measures to counter program discontinuation. Despite small differences in divisional responses, the results supported the existence of institutional isomorphism when unified program values (e.g., academics, conduct, community involvement) were consistent across all NCAA divisions.